Widowed parenting self-efficacy scale: A new measure - Edwards, Teresa P. (Death Stud, 2017)
The authors developed and tested a novel measure of parenting self-efficacy specifically for recently widowed parents of dependent-age children. They tested the scale among 244 recently widowed fathers via an open-access web survey. Exploratory factor analysis identified 3 factors: perception of meeting parenting expectations (α = .88), provision of effective discipline (α = .69), and sense of parental burden (α = .69). Scores on the new scale correlated positively with Kansas Parenting Satisfaction and Psychological Adaptation Scale scores, and negatively with CES-D (depression) and TRIG (grief) scale scores. The resulting 9-item Widowed Parenting Self Efficacy Scale is a promising measure for use in research and clinical settings.